Static and free vibration analysis of leaf springs by finite element method - Chen, Jun (Nanyang Technological University, 2022)
Leaf springs are essential components in some of the suspension systems. They are mainly used in heavy-duty vehicles, railroad carriages, trucks, and many SUVs nowadays. The function of the leaf spring is to absorb and store energy to then release it just like all other springs. When leaf spring undergoes loading conditions, the spring experiences stress and deflection. To prevent failure, the maximum stress experienced by the spring must be lower than the yield stress of the material and the maximum deflection must also be less than a certain maximum permissible deflection.